Shear Wave Measurements of a Gelatin’s Young’s Modulus - Pansino, Stephen; Taisne, Benoit (Frontiers in Earth Science, 2020)
We present a technique to measure the Young’s modulus of a gelatin, using shear waves. Gelatin is a commonly used material for analogue experiments in geophysics, investigating fluid-filled fractures like magmatic dikes, as well as fault slip. Using polarized filters, the deviatoric stresses in a block of gelatin become visible, as do the stress perturbation induced by waves propagating through the medium. We demonstrate how the wave velocity can be measured and related to the Young’s modulus, as well as processing techniques that improve the measurement precision. This methodology is simple to implement into a laboratory setting, can make precise, time-efficient estimates of the material strength and additionally is non-destructive and can be performed in situ.